Long non‐coding RNA CRALA is associated with poor response to chemotherapy in primary breast cancer. Issue 6 (23rd August 2017) - Li, Yudong; Wang, Baoxiao; Lai, Hongna; Li, Shunying; You, Qiuting; Fang, Yichao; Li, Qian; Liu, Yujie
Abstract : Background: Breast cancer is the most commonly diagnosed cancer in women, and has become the second leading cause of cancer death among women worldwide. Chemoresistance has become an important problem in breast cancer clinics. The identification of new mechanisms affecting chemosensitivity is of great clinical value for the treatment of breast cancer. Methods: The expression levels of chemoresistance‐associated long non‐coding RNA (CRALA), a newly discovered long non‐coding RNA, were measured by quantitative real time‐PCR in 79 pre‐treatment biopsied primary breast cancer samples. Small interfering RNAs were used to knockdown CRALA expression. The effect of CRALA on chemosensitivity was evaluated using cell growth assay. Results: Non‐responding tumors (poor response to chemotherapy, 32 samples) had fourfold higher CRALA expression than responding tumors (good response to chemotherapy, 47 samples). CRALA is upregulated in chemoresistant breast cancer cell lines compared to their parental lines. Silencing of CRALA in chemoresistant breast cancer cells resensitizes the cells to chemotherapy in vitro. Furthermore, univariate and multivariate analysis showed that higher CRALA expression was significantly associated with poor prognosis in 144 breast cancer patients. Conclusion: The study findings indicate that CRALA expression may be an important biomarker for predicting the clinical response to chemotherapy and prognosis in breast cancer patients. It is possible to target CRALA to reverse chemoresistance in breast cancer patients.